A=x2-2xy+y2
B=3xy-y2+5x2
a, Tính :A+B
b, Tính :A-B
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A-B-C=\left(-x^2+3xy+2y^2\right)-\left(4x^2-5xy+3y^2\right)-\left(3x^2+2xy+y^2\right)\)
\(=-x^2+3xy+2y^2-4x^2+5xy-3y^2-3x^2-2xy-y^2\)
\(=-8x^2+6xy-2y^2\)
Ta có
C − A − B = − x 2 + 3 x y + 2 y 2 − 4 x 2 − 5 x y + 3 y 2 − 3 x 2 + 2 x y + y 2 = − x 2 + 3 x y + 2 y 2 − 4 x 2 + 5 x y − 3 y 2 − 3 x 2 − 2 x y − y 2 = − x 2 − 4 x 2 − 3 x 2 + ( 3 x y + 5 x y − 2 x y ) + 2 y 2 − 3 y 2 − y 2 = − 8 x 2 + 6 x y − 2 y 2
Chọn đáp án B
a) Ta có: \(M+\left(5x^2-2xy\right)=6x^2+9xy-y^2\)
\(\Leftrightarrow M=6x^2+9xy-y^2-5x^2+2xy\)
\(\Leftrightarrow M=x^2+11xy-y^2\)
Vậy: \(M=x^2+11xy-y^2\)
b) Ta có: \(\left(3xy-4y^2\right)-N=x^2-7xy+8y^2\)
\(\Leftrightarrow N=3xy-4y^2-x^2+7xy-8y^2\)
\(\Leftrightarrow N=-x^2+10xy-12y^2\)
Vậy: \(N=-x^2+10xy-12y^2\)
a, (6x2+9xy-y2) - ( 5x2-2xy)=M
=> M= (6x2+9xy-y2) - ( 5x2-2xy)
=> M= 6x2+9xy-y2 - 5x2+2xy
=> M=(6x2- 5x2)+(9xy+2xy)-y2
=>M= 1x2 + 11xy - y2
Vậy M= 1x2 + 11xy - y2
b, N= (3xy-4y2) - (x2-7xy+8y2)
=> N= 3xy-4y2 - x2+7xy-8y2
=> N= (3xy+7xy)-(4y2+8y2)-x2
=> N= 10xy - 12y2 -x2
Vậy N= 10xy - 12y2 -x2
a: Ta có: \(M+5x^2-2xy=6x^2+9xy-y^2\)
\(\Leftrightarrow M=6x^2+9xy-y^2-5x^2+2xy\)
\(\Leftrightarrow M=x^2+11xy-y^2\)
b: Ta có: \(\left(3xy-4y^2\right)-N=x^2-7xy+8y^2\)
\(\Leftrightarrow N=3xy-4y^2-x^2+7xy-8y^2\)
\(\Leftrightarrow N=-x^2+10xy-12y^2\)
kho quá
Mk giải đc rùi